Mpox in patients attended in the Sexually Transmitted Diseases Sector of the Universidade Federal Fluminense in the municipality of Niterói (RJ), Brazil - Arze, Wilma Nancy Campos; Paixão, Izabel Christina Nunes de Palmer; Pessanha, Claudio Cesar Cirne dos Santos; Rabelo, Kíssila; Leão, Maurício de Souza; Andrade, Hugo Boechat; Silva, Ingrid Antunes da; Bittar, Christina Thereza Machado; Carvalho, Jorge José de; Goulart, Aline Gissele Azevedo Ferreira; Campos, Lucas Gabriel Cabrera; Campos, Adriel Chihyung Chung; et al. (Brazilian Journal of Sexually Transmitted Diseases, 2025)
Introduction: Mpox, formerly known as monkeypox, is caused by the double-stranded DNA MPXV virus of the Poxviridae family, Orthopoxvirus genus. It has two known clades: West Africa and Congo Basin. It is a zoonosis similar to smallpox that has reemerged globally, with numerous cases reported worldwide in 2022. Objective: To describe sociodemographic, behavioral, clinical, and laboratory characteristics of suspected and confirmed mpox cases attended in the Sexually Transmitted Diseases (STD) Sector of the Fluminense Federal University (UFF), Niterói (RJ), Brazil. Methods: The STD/UFF sector is a public open-access reference center for STDs, with no appointment regulation. This is a prospective, observational cohort study of suspected and confirmed MPXV cases attended at STD/UFF between June 2022 and March 2024. Clinical samples (lesions) were collected for diagnostic confirmation by MPXV reverse transcription-polymerase chain reaction — RT-PCR (public laboratory — LACEN-RJ), along with rapid tests for syphilis, human immunodeficiency virus (HIV), and hepatitis B and C. Results: Among 33 individuals with suspected mpox, 20 (60.6%) were confirmed. Compared to non-confirmed cases, confirmed cases were more frequent among unvaccinated individuals aged 21–39 years, cisgender men (70 vs. 69.15%; p<0.015), Black individuals (55 vs. 45%; p=0.449), residents of São Gonçalo (50 vs. 30.8%; p=0.335), those with higher education (45 vs. 30.8%; p=0.429), and men who have sex with men (MSM) (80 vs. 53.84%; p=0.508). They were more likely to have a non-exclusive steady partner (50 vs. 7.69%; p=0.233), good knowledge and preventive practices regarding STIs (75 vs. 46.15%; p=0.204), to use condoms occasionally (80 vs. 61.54%; p=0.500), to have been referred by a health professional (70 vs. 61.54%; p<0.041), and to have syphilis as the main differential diagnosis (30 vs. 30.77%; p=0.415). Confirmed cases more often presented genital (60 vs. 39.8%) and anal lesions (85 vs. 30.8%) and systemic symptoms (93.2 vs. 69.3%) than non-confirmed ones. Forty-five percent were HIV-positive white males over 32 years old, MSM, with anal lesions, and 33.33% were diagnosed with syphilis. Among the mpox-positive cases, 27% reported pre-exposure prophylaxis (PrEP) use and 9% post-exposure prophylaxis (PEP) use. Of these, 65% had their sexual partners examined at STD-UFF, with 38.46% testing positive for mpox. There were no severe cases or hospitalizations. Conclusion: Mpox in Rio de Janeiro rapidly evolved into a local epidemic, with sexual contact playing a crucial role in its spread, and higher incidence among MSM and people living with HIV (PLHIV). The rate of sexual partner consultation and testing in our service was high, and comorbidity with syphilis was frequent.